Effect of Deformable Gurney Flaps on the Output Power of Flapping Turbine - Chebana Abdelbasset; Ghelani Laala; Mohamed Taher Bouzaher; Charaf Eddine Bensaci; Alaeddine Zereg; Nadhir Lebaal; Mounir Aksas (Fluids)
The Gurney flap (GF) is a simple flat plate frequently mounted at the airfoil rear. Several investigations have been devoted to studying the effect of a rigid or even movable GF on the aerodynamic behavior of several devices such as flapping airfoils and vertical or horizontal axis turbines. The present paper proposes a new concept of a deformable Gurney flap (DGF) to improve the output power of a flapping airfoil in vertical mode. The advantage of this model is the full control of the effect on the GF during the flapping movement. The DGF is expandable and contractible which allows for monitoring and adjusting the pressure distribution at the appropriate time and position. By using a 2D transient simulation with a specific dynamic mesh design, an extended numerical analysis has been provided. It was found that this model is able to increase the output power by 19.5%. Furthermore, the concept of the DGF is applied on flapping turbines in hybrid modes such as swing arm mode and D-shaped mode. These modes are investigated to clarify the studied model’s advantage and to demonstrate the possibility of applying this strategy to control the different flapping movements.